ALGORITHMIC CURATION'S INFLUENCE ON IMPULSIVE BUYING: MEDIATING ROLE OF URGE IN TIKTOK - Nadroh, Ummi; Nurrohman, Rosyid; Hakim, Ahmad Firman (GEMAH RIPAH: Jurnal Bisnis, 2026)
The rapid growth of TikTok Live commerce has revolutionized online shopping. This study examines the role of perceived algorithmic curation intensity in driving impulsive buying in TikTok Live commerce, with urge to buy as a mediating variable. The objective of this research is to understand how algorithmic curation impacts consumer impluse buying in a live-streaming shopping context. The survey involved 100 TikTok users from Samarinda and Balikpapan, who had previously engaged in product purchases during TikTok Live sessions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that perceived algorithmic curation intensity positively influences urge to buy, which in turn significantly drives impulsive buying. The analysis revealed that perceived algorithmic curation intensity positively influences urge to buy (path coefficient = 0.502), which in turn strongly affects Impulsive Buying (path coefficient = 0.785). The model explained 61.6% of the variance in impulsive buying behavior, highlighting the significant role of emotional triggers in driving consumer purchases.